Semiotic space of economic culture - Вихованець, З. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article analyzes the cognitive communicative-language practices in the sphere of man’s social and economic life. The language potentiality accumulates all possible knowledge of real human communities, indirectly reflecting the deep structures of their social and economic being. The knowledge mentioned above acquires a unique consistency and coherence within a language. It is a reason of relative autonomy of law tendencies of existence of language itself and it enables cooperation between people in the sphere of the economic activity.